MENINGKATKAN KOSA KATA DENGAN MENGGUNAKAN SISTEM CERITA - Rahmadi, Nizar; Sulan, Kasiman (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
The main objective of this research was to find out whether using the Story System can improve students’ vocabulary in the tenth grade of SMA Ar-Rahim Pontianak. This research used a pre-experimental design with 160 students of SMA Ar-Rahim Pontianak. This research used 31 students as a sample a random sampling technique and used multiple choice and essay as the instruments of research. The result showed the score on – the test 62.83 was higher than the mean score on the – test 39.48 and the t-test value was greater than the–table (17.55 > 2.042) It means that the Story System is one of a good technique in teaching vocabulary because it is prove using story system was effective to improve students’ vocabulary.